Current-voltage and capacitance-voltage characteristics of the ITO/polyaniline doped boron trifloride/Al Schottky diode - Yakuphanoğlu, Fahrettin; Senkal, B. Filiz (Wiley, 2008)
The electrical characteristics of the ITO/polyaniline (PANI) doped boron trifloride (BF3)/Al Schottky diode have been investigated by current-voltage (I-V) and capacitance-voltage (C-V) methods. The diode indicates a rectification behavior with the ideality factor of 4.78. An ideality factor higher than unity can result from the interface state and electronic properties of the PANI doped BF3 organic semiconductor. The barrier height of the diode was determined from both I-V and C-V characteristics. The barrier height obtained from the C-V measurements is higher than that obtained from the I-V measurements. At higher forward bias voltages, the space charge-limited current is the dominant transport mechanism, whereas at reverse bias voltages, the current flow in the ITO/PANIBF(3)/Al diode is controlled by Schottky emission mechanism. Copyright (C) 2008 John Wiley & Sons, Ltd.
Keywords: Schottky diode; organic semiconductor; polyaniline doped boron trifloride